WASHBACK OF THE ENGLISH SECTION OF COLLEGE ENTRANCE EXAM ON THE STUDENTS’ PRODUCTIVE AND RECEPTIVE SKILLS - Wulandari, Fitri Wulandari (Jurnal Smart, 2016)
Exam plays a powerful role in educational system and exerts significant washback on students’ learning. Washback, the impact of exams on education in general and language examining in particular, has become a popular area of study within educational research. This paper focuses on the washback effects of college entrance exam on students’ productive and receptive skills in STKIP Muhammadiyah Pringsewu Lampung. The main concern of the study was to investigate the impact of college entrance exam on productive and receptive language skills in STKIP Muhammadiyah Pringsewu Lampung. 53 first year students at English Education Department in the academic year of 2015-2016 of STKIP Muhammadiyah Pringsewu Lampung attended the study. A 26-item questionnaire was designed and administered to 53 students. The data were analyzed using statistical analysis including descriptive statistics (frequency, percentage, mean, and standard deviation). It has been found out that the exam has some negative effects on students’ language productive and receptive skills on the first year students at English Education Department of STKIP Muhammadiyah Pringsewu Lampung. Some changes to exam that might be grateful are discussed in the last section of the paper. Keywords: washback effect, college entrance exam, students’ productive skills